(untitled) (Revista de Estudos da Linguagem, 2007)
This study focuses on the uses of the past imperfect tense of thesubjunctive according to data provided by VARSUL,1 on the basis ofBello’s prepositions (1979 [1841], 1984 [1847]) regarding Spanish.In this sense, an analysis semantic-pragmatic has been conducted inorder to interpret the evidence furnished by the Portugueseflorianopolitano which shows a metaphoric process at work.